Perluasan dan Penerapan Asas Ne Bis In Idem dalam Hukum Pidana Indonesia - Nazhif Ali Murtadho (Jurnal Ilmiah Kebijakan Hukum, 2026)
The fundamental inconsistency in the application of the principle of ne bis in idem between written regulations and judicial practice, both in litigation and non- litigation disputes, risks giving rise to repeated prosecutions that undermine the guarantee of legal certainty. This study analyzes the expansion of this principle within the framework of restorative justice in the New Criminal Procedure Code and its historical dynamics from the Colonial Criminal Code to the National Criminal Code. The method used is a type of doctrinal legal research through a statutory approach, a conceptual approach, and a case approach with a deductive legal material analysis technique. The findings indicate a terminological shift from "act" to "same case" in the National Criminal Code that orients the benchmark on the unity of legal identity based on strafrechtevjke betekenis, as well as the integration of the principle of una via to prevent the cumulation of sanctions. Furthermore, the New Criminal Procedure Code expands the scope of this principle by integrating restorative justice mechanisms through a victim- offender mediation model, thereby obtaining an official court determination as a final, closed-the-case status based on the principle of lex superior derogat legi inferiori. In conclusion, the reconceptualization of the ne bis in idem principle has transformed its traditional function into a progressive normative foundation that guarantees substantive justice and definitive finality in cases. This study recommends the drafting of a Law or Government Regulation on Restorative Justice that emphasizes the ne bis in idem clause for cases that have been resolved through the restorative justice stage.